PENGARUH JAM KERJA DAN PENGALAMAN KERJA TERHADAP PENDAPATAN FOTOGRAFER PADA OBYEK WISATA TANAH LOT KECAMATAN KEDIRI KABUPATEN TABANAN - I WAYAN MULA SARJANA (Universitas Mahasaraswati Mataram, 2019)
Bali as an agricultural area with most of the population works as farmers, but along with the development of tourism, the population starts working in the tourism sector. Since the beginning of its development, tourism in Bali has been declared a cultural tourism imbued with Hinduism. One of the tourist attraction areas in Bali which is famous for the development of cultural tourism is the Tanah Lot area, located in Tabanan Regency. The purpose of this study is to determine the effect of working hours and work experience on the income of photographers in the Tanah Lot Tourism Object Area. The number of samples taken is 55 respondents. The analysis technique used is multiple linear regressions. Simultaneous analysis results show that the variable hours of work and work experience significantly influence the income of photographers in the Tanah Lot Tourism Object Area. While the partial analysis results, variable hours of work and work experience significantly affect the income of photographers in the Tanah Lot Tourism Object Area. R Square = 0.856 which means 85.6 percent of the influence of the rise and fall of the photographer's income in the Tanah Lot Tourism Object Area is influenced by working hours and work experience, the remaining 14.4 percent is influenced by other variables not explained in this model.